Hardness and mineralogical composition of rocks in open pit mining (Czech Journal of Multidisciplinary Innovations, 2024)
In mining enterprises, it is necessary to pay attention to the physico-mechanical and chemical composition of rocks during the open mining of minerals. For this, it is appropriate to study the hardness coefficient of rocks. In open pit mining, we can see the properties of rocks such as hardness, brittleness, scratchability. When mining rocks, we need to determine the mechanical impact of mining vehicles on the excavated part of the ore body. In most mines, the coefficient of strength of rocks is determined depending on the location coordinates of the mineral. In order to completely separate the ore body from the layer, it is necessary to separate the ore from the layer without damaging it. This prevents loss of ore and deterioration of ore in the mining enterprise.